Competition in funding higher education - Bernhard Eckwert; Itzhak Zilcha (Center for Economic Studies and ifo Institute (CESifo), 2011)
In higher education pure credit market funding leads to underinvestment while income-contingent loans funding tends to produce overinvestment. We analyze whether a market structure in which both funding schemes coexist and compete against each other might restore efficiency of the educational investment process. In the absence of government intervention, we find that funding competition does not rectify the investment inefficiency nor will it improve pooling of individual income risks. However, a policy which allows the two financing schemes to compete and which, at the same time, restricts access to higher education can achieve investment efficiency and improve risk pooling. We find that the equilibrium with funding competition and restricted participation yields the highest level of social welfare.
Keywords: D31; H31; I22; 330; higher education; funding competition; human capital formation